Prevalence of Subclinical Mastitis in Gir Cows in and around Junagadh District of Gujarat - Patel, Bhavika R; Vagh, Arshi A; Vala, Karshan B; Patel, Ashish C (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The research was conducted to determine the prevalence of subclinical mastitis among Gir cows in the vicinity of Junagadh. A total 990 quarters of 250 lactating Gir cows were screened by using California mastitis test. Overall animal wise prevalence of SCM was 32.80% and quarter wise prevalence 22.32% in lactating Gir cows. The prevalence of subclinical mastitis was highest in the right fore quarter (28.40%), followed by the right hind quarter (24.29%), left fore quarter (19.43%), and left hind quarter (17.07%). SCM was more prevalent in the right side quarters (26.36%) compared to the left side quarters (18.26%) and fore quarters having a greater prevalence (23.94%) than hind quarters (20.69%). The animal wise and quarter wise prevalence of SCM in relation to age was highest in 5-7 year old Gir cows (38.78% and 27.32%). The animal wise and quarter wise prevalence of SCM in relation to lactation number was highest in fourth lactation (41.27% and 32.00%) and the least in sixth and above lactations (19.05% and 15.66%). The animal and quarter wise prevalence of SCM in relation to stage of lactation was highest in early lactation (41.41% and 27.74%) followed by mid lactation (30.34% and 21.47%) and late lactation (22.58% and 14.81%).